Guide sheath versus non-guide sheath method for endobronchial ultrasound-guided biopsy of peripheral pulmonary lesions: a multicentre randomised trial. Issue 5 (26th May 2022) - Oki, Masahide; Saka, Hideo; Imabayashi, Tatsuya; Himeji, Daisuke; Nishii, Yoichi; Nakashima, Harunori; Minami, Daisuke; Okachi, Shotaro; Mizumori, Yasuyuki; Ando, Masahiko
Background: Guide sheaths (GSs) have been widely used during radial probe endobronchial ultrasound-guided transbronchial biopsy (rEBUS-TBB) of peripheral pulmonary lesions. However, it remains unknown whether a GS enhances the diagnostic yield. We compared the diagnostic yields of small peripheral pulmonary lesions between rEBUS-TBB with and without a GS. Methods: In eight institutions, patients with peripheral pulmonary lesions ≤30 mm in diameter were enrolled and randomised to undergo rEBUS-TBB with a GS (GS group) or without a GS (non-GS group) using a 4.0-mm thin bronchoscope, virtual bronchoscopic navigation and fluoroscopy. The primary end-point was the diagnostic yield of the histology specimens. Results: A total of 605 patients were enrolled; ultimately, data on 596 (300 in the GS group and 296 in the non-GS group) with peripheral pulmonary lesions having a longest median diameter of 19.6 mm were analysed. The diagnostic yield of histological specimens from the GS group was significantly higher than that from the non-GS group (55.3% versus 46.6%; p=0.033). Interactions were evident between the diagnostic yields, procedures, lobar locations (upper lobe versus other regions; p=0.003) and lesion texture (solid versus part-solid nodules; p=0.072). Conclusions: The diagnostic yield for small peripheral pulmonary lesions afforded by rEBUS-TBB using a GS was higher than that without a GS. Use of a guide sheath during endobronchial ultrasound-guided transbronchial biopsy enhances the diagnostic yield for small peripheral pulmonary lesions https://bit.ly/3utOUHk